Food insufficiency and food insecurity as risk factors for physical disability among Palestinian refugees in Lebanon: Evidence from an observational study. Issue 4 (October 2016) - Salti, Nisreen; Ghattas, Hala
Abstract: Background: Potential interactions between malnutrition and disability are increasingly recognized, and both are important global health issues. Causal effects working from nutrition to disability and from disability back to nutrition present an empirical challenge to measuring either of these effects. However, disability affects nutrition whatever the cause of disability, whereas nutrition is likelier to affect disease-related disability than war- or work-related disability. Objective: This paper investigates the association of food insufficiency with the risk of physical disability. Data on disability by cause allow us to address the difficulty of reverse causality. Methods: Multinomial logit regressions of disability by cause on food insufficiency are run using survey data from 2010 on 2575 Palestinian refugee households in Lebanon. Controls include household sociodemographic, health and economic characteristics. Regressions of food insufficiency on disability by cause are also run. Results: Disability has a significant coefficient in regressions of food insufficiency, whatever the cause of disability; but in regressions of disability on food insufficiency, food insufficiency is significant only for disease-related disability (log odds of disease-related disability .78 higher, p = .008). The difference in the results by cause of disability is evidence of a significant association between food insufficiency and disease-related disability, net of any reverse effect from disability to food access. Conclusions: The association between disease-related disability and food insufficiency is statistically significant suggesting that even taking into account feedback from disability to nutrition, nutrition is an effective level of intervention to avert the poverty-disability trap resulting from the impoverishing effect of disability.